(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To describe the process of construction and validation of Nurseostomy, a nursing assessment instrument for individuals with intestinal ostomy in a hospital setting. Method: This is a methodological study developed following the recommendations of the Brazilian Consensus on Care for Adults with Elimination Ostomies to support the construction of the assistive technology and the validation of content, structure, and appearance with experts. The tool was developed using Microsoft Word®. The study participants were 17 stoma care nurse experts. Data collection took place between October and November 2022 using a Google Forms questionnaire. For data analysis, the Content Validity Index (CVI) was used, with a minimum agreement value of 0.8. Results: An instrument consisting of seven domains was developed according to the Wanda de Aguiar Horta theoretical framework. The global CVI was 0.91. Conclusion: The instrument was considered validated in all three axes (content, structure, and relevance) and shows potential for external validation and the development of clinical research.